Pharmacodynamics of Ceftriaxone, Ertapenem, Fosfomycin and Gentamicin in Neisseria gonorrhoeae - Urša Gubenšek; Myrthe de Laat; Sunniva Foerster; Anders Boyd; Alje Pieter van Dam (MDPI AG, 2022)
Objectives: To assess the in vitro effect of select antimicrobials on the growth of N. gonorrhoeae and its pharmacodynamic parameters. Methods: Time-kill assays were performed on two reference N. gonorrhoeae strains (ceftriaxone-resistant WHO X and ceftriaxone-susceptible WHO F) and one clinical N. gonorrhoeae strain (ceftriaxone-susceptible CS03307). Time-kill curves were constructed for each strain by measuring bacterial growth rates at doubling antimicrobial concentrations of ceftriaxone, ertapenem, fosfomycin and gentamicin. Inputs from these curves were used to estimate minimal bacterial growth rates at high antimicrobial concentrations (ψmin), maximum bacterial growth rates in the absence of antimicrobials (ψmax), pharmacodynamic minimum inhibitory concentrations (zMIC), and Hill's coefficients (κ). Results: Ceftriaxone, ertapenem and fosfomycin showed gradual death overtime at higher antimicrobial concentrations with a relatively high ψmin, demonstrating time-dependent activity. Compared to WHO F, the ψmin for WHO X was significantly increased, reflecting decreased killing activity for ceftriaxone, ertapenem and fosfomycin. At high ceftriaxone concentrations, WHO X was still efficiently killed. CS03307 also showed a high ψmin for ceftriaxone in spite of a low MIC and no difference in ψmin for fosfomycin in spite of significant MIC and zMIC differences. Gentamicin showed rapid killing for all three strains at high concentrations, demonstrating concentration-dependent activity. Conclusions: Based on time-kill assays, high-dosage ceftriaxone could be used to treat N. gonorrhoeae strains with MIC above breakpoint, with gentamicin as a potential alternative. Whether ertapenem or fosfomycin would be effective to treat strains with a high MIC to ceftriaxone is questionable.